Frontal two-electrode transcranial direct current stimulation protocols may not affect performance on a combined flanker Go/No-Go task - Holczer Adrienn; Vékony Teodóra; Klivényi Péter; Must Anita (2023)
Transcranial direct current stimulation (tDCS) has been tested to modulate cognitive control or response inhibition using various electrode montages. However, electrode montages and current polarities have not been systematically compared when examining tDCS effects on cognitive control and response inhibition. In this randomized, sham-controlled study, 38 healthy volunteers were randomly grouped into receiving one session of sham, anodal, and cathodal each in an electrode montage that targeted either the dorsolateral prefrontal cortex (DLPFC) or the fronto-medial (FM) region. Participants performed a combined flanker Go/No-Go task during stimulation. No effect of tDCS was found in the DLPFC and FM groups neither using anodal nor cathodal stimulation. No major adverse effects of tDCS were identified using either montage or stimulation type and the two groups did not differ in terms of the reported sensations. The present study suggests that single-session tDCS delivered in two two-electrode montages might not affect cognitive control or response inhibition, despite using widely popular stimulation parameters. This is in line with the heterogeneous findings in the field and calls for further systematic research to exclude less reliable methods from those with more pronounced effects, identify the determinants of responsiveness, and develop optimal ways to utilize this technique.
Keywords: Klinikai orvostan